Dominant Factors That Influence the Interest of Gemati Tennis Academy Members - Danuarta, Pramudya Bagas; Sceisarriya, Vega Mareta; Pratama, Henri Gunawan; Febrianto, Nendra (Indonesian Journal of Sport, Health and Physical Education Science, 2026)
Background: The increasing interest in tennis has contributed to the growth of local sports clubs, including the Gemati Tennis Academy in Trenggalek Regency, East Java. As a community-based sports organization, the academy supports technical skill development, character building, and active lifestyles. However, variations in members’ participation levels indicate that different factors may influence their interest in tennis training activities. Methods: This study employed a quantitative descriptive design using a survey method. The participants were all 49 members of the Gemati Tennis Academy selected through total sampling. Data were collected using a closed-ended questionnaire covering 12 variables related to internal, external, and supporting factors. The instrument was tested for validity and reliability. Data analysis was conducted using Principal Component Analysis (PCA) with the assistance of SPSS software. Result: The results of the PCA identified three dominant factors influencing members’ interest in tennis training. Internal factors had the highest eigenvalue (4.674), indicating the strongest influence, followed by external factors (eigenvalue = 1.361) and supporting factors (eigenvalue = 1.164). These factors were extracted from the 12 observed variables and explained the structure of members’ training interest. Conclusion: Members’ interest in tennis training at the Gemati Tennis Academy is influenced by internal, external, and supporting factors, with internal factors being the most dominant. These findings provide valuable insights for coaches and club managers in developing effective and sustainable training programs to enhance member participation.